1997
DOI: 10.1038/sj.bjp.0701091
|View full text |Cite
|
Sign up to set email alerts
|

Simulatory effect of porcine insulin on noradrenaline secretion in guinea‐pig ileum myenteric nerve terminals

Abstract: 1 The eect of insulin on the release of noradrenaline (NA) from nerve terminals was investigated in isolated ileal synaptosomes of guinea-pig. Release was determined as the amount of NA, quanti®ed by h.p.l.c.-electrochemical detection, from samples incubated with insulin minus that in parallel blanks treated with some volume of vehicle. 2 Porcine insulin stimulated the secretion of NA in a concentration-dependent manner from 0.01 i.u. ml 71 , while the value of lactate dehydrogenase in the incubated medium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Insulin has been demonstrated to increase noradrenaline release from sympathetic nerves in the guinea pig ileum (Cheng et al, 1997). This increase may be due in part to inhibition of neuronal M 2 muscarinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin has been demonstrated to increase noradrenaline release from sympathetic nerves in the guinea pig ileum (Cheng et al, 1997). This increase may be due in part to inhibition of neuronal M 2 muscarinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is both clinical and experimental evidence that sympathetic dysfunctions are implicated in the pathophysiology of several digestive orders (McIntyre & Thompson, 1992). Previous studies have shown that noradrenergic nerve terminals supplying the digestive tract are equipped with presynaptic heteroreceptors, including muscarinic, opioid and insulin receptors (Fuder & Muscholl, 1995; Cheng et al ., 1997), the activation of which results in positive or negative changes of noradrenaline release. However, the possibility that prejunctional histamine receptors participate in the control of intestinal sympathetic neurotransmission has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%